2013
DOI: 10.1212/wnl.0b013e3182824e66
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of intranasal ketamine in migraine with prolonged aura

Abstract: This study provides class III evidence that intranasal ketamine is effective in reducing aura severity in patients with migraine with prolonged aura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 38 publications
1
110
0
5
Order By: Relevance
“…These findings suggest that excitatory amino acid receptors (and NMDA in particular) play an important role in pain processing and the sensitization process which is also present in migraineurs (Vikelis and Mitsikostas, 2007). Ketamine, an NMDA antagonist, is so far the only promising treatment option for patients with severe or long-lasting migraine aura (Afridi et al, 2013). Another novel substance, tezampanel, which acts on the AMPA and kainate subtypes of ionotropic glutamate receptors (Alt et al, 2006), has also shown promising results in acute migraine therapy (Sang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that excitatory amino acid receptors (and NMDA in particular) play an important role in pain processing and the sensitization process which is also present in migraineurs (Vikelis and Mitsikostas, 2007). Ketamine, an NMDA antagonist, is so far the only promising treatment option for patients with severe or long-lasting migraine aura (Afridi et al, 2013). Another novel substance, tezampanel, which acts on the AMPA and kainate subtypes of ionotropic glutamate receptors (Alt et al, 2006), has also shown promising results in acute migraine therapy (Sang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…32 Intranasal ketamine also reduces the severity of pain in migraine. 33 Wink et al 34 reported a 29-year-old woman with autism who was treated with intranasal ketamine (20-60 mg) on 12 dosing occasions across 6 weeks. She showed improvements in mood, social interactions, flexibility, tolerance of changes in routine, motivation, and concentration.…”
Section: Intranasal Ketaminementioning
confidence: 99%
“…Unfortunately, effective treatments for aura signs and symptoms (in particular for those patients with substantial disability due to aura duration and severity) are not yet well established. Up to now, intranasal ketamine has shown to be effective in reducing severity (but not duration) of long-lasting aura [10]. Moreover, small studies or isolated case reports supported the role of a series of drugs in aborting migraine aura [11] [12] in modulating migraine with aura in particular, but none of these treatments is currently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%